Intra-Africa trade and the need to rethink the neo-liberal approach - Ngwu, Franklin; Ojah, Kalu (Transnational Corporations Review, 2024)
Notwithstanding past trade reforms, trade in Africa and particularly intra-Africa trade, remain dismal. Africa has even created economic communities, fitted with monetary, fiscal, and socio-political anchors, by way of various Regional Economic Communities (RECs) – now reflected by the African Continental Free Trade Area (AfCFTA). Whilst these have yielded marginal benefits, the persistence of low intra-Africa trade calls into question their suitability. Focused on the realities of institutions targeted by these reforms and Africa's context – i.e., weak linkages between institutions, high informality, and low social capital – we posit that reforms have not elicited the hoped-for high intra-Africa trade because of their near total reliance on the neo-liberal approach, which neglects Africa's context. Drawing on Africa's sociology and new institutional economics, we use a conceptual institutional analysis to evolve a political economy based framework that suggests potential solutions: Linking the formal sector that currently underpins economic/trade policies to the informal institutions that are reflective of Africa's norms, values, cultures and expectations (the informal sector), and scaling up production; via the cooperatives production model, strategic procurement mandates, and effectuation of continental transportation infrastructure network, are our recommended pathways to reversing the current dismal intra-continental trade.
Keywords: Africa; Africa's sociology; Growth and trade policies; Institutional economics; Intra-Africa trade

Beyond free trade in raw materials: Reconciling international trade rules with planetary boundaries - Kuppuswamy, Chamundeeswari; Boklan, Daria (The Extractive Industries and Society, 2024)
International trade rules enshrined in agreements like the General Agreement on Tariffs and Trade (GATT) promote free trade, with exceptions for environmental protection. This paper explores the tension between these rules and Earth Systems Science's concept of planetary boundaries, which define environmental tipping points beyond which humanity faces irreversible harm. We analyse GATT's provisions, particularly Article XI's prohibition on trade restrictions and Article XX's exceptions, through the lens of planetary boundaries. Our analysis argues that current interpretations of these articles are inadequate to address the environmental impact of raw material trade. We further examine the concept of permanent sovereignty over natural resources, which grants states autonomy over resource exploitation and trade. We posit that planetary boundaries are not a restriction on sovereignty but a call for modifying state trading behaviour and consequently how international trade rules is structured and interpreted. This analysis demonstrates the complexity of transforming the legal landscape necessary for a global just energy transition, a response to climate change that requires aligning international trade with environmental sustainability.
Keywords: Climate change; GATT Art. XX; No-harm principle; PSNR; Planetary boundaries; WTO trade rules

Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

African Continental Free Trade Area and Regional Trade in ICT and Digital Technologies - Adams, Kweku; Attah-Boakye, Rexford; Yu, Honglan; Chu, Irene; Mali, Dafydd (Journal of International Management, 2024)
This study examines the impact of the African Continental Free Trade Area (AfCFTA) on regional trade in the Information and Communication Technology (ICT) and Digital Technologies (DT) sector across 43 African countries from 2014 to 2021. Employing the augmented gravity model and confidence-level estimations, it highlights AfCFTA's mediating role in enabling ICT&DT trade on the continent. Using hierarchical regression analysis of a panel dataset comprising 5,160 observations, the findings imply that trade openness and productive capacities not only facilitate trade in the ICT&DT sector but also result in positive spillover effects across various economic sectors. This study contributes to the international business literature by refining the application of the gravity model to capture the need for sector-specific analyses to unpack institutional dynamics and dis-enablers of trade. It identifies AfCFTA as a pivotal yet underexplored element in the global trade landscape, highlighting its potential as Africa seeks a more prominent role on the global stage. The research stresses the significance of digital empowerment and policy reforms to maximise the benefits of regional integration under AfCFTA.
Keywords: AfCFTA; ICT and digital technologies; Regional trade; Trade enablers; Trading bloc

Multilateralism and Bilateralism in International Trade - Aro, Gilbert; Nwosu, Chiedozie; Ngene, Innocent; Nnadi, Samuel (African Journal of Politics and Administrative Studies, 2024)
The contemporary international system is dominated by international trade. Therefore, it is the fundamental and critical aspect of international economic relations. The study investigated the how African states participate in common bilateral and multilateral trade relations. Its core objective is to study whether trade barriers have been made less cumbersome among the participating countries in African continental region. Common trade and international trade justify the essence of globalization. The wave of globalization has necessitated the flux of multilateralism and bilateralism among the participating nations in the international trade. Methodologically, the study adopted comparative theory of international trade. Its method of data collection is documentary method and analyzed through interpretive studies. As the international trade continues to take the centre stage in the international economic relations; States continue to engage in multilateral and bilateral trade relations. The operations of Transnational Corporations (TNCs) and Multi-national Corporations (MNCs) as non-state actors also engage in multilateral and bilateral agreements with the host states. Several agreements led to the establishment of General Agreement on Tariff and Trade (GATT) and World Trade Organization (WTO) remains conspicuous products of multilateralism and bilateralism in the international trade in the recent time. African Continental Free Trade Area (AFCFTA) is a multilateral agreement enacted by fifty-four members of the African Union (AU) in 2019 to boost trade relations among them. Its core benefit is to facilitate free trade and removal of trade barriers in the region Therefore, this study is set to examine the advantages and impacts of AFCFTA and other multilateral and bilateral agreements in Africa and the world at large.
Keywords: AfCFTA; Bilateralism; International Trade; Multilateralism; Trade agreements; WTO

Nigeria-China Relations and Economic Development - Chiedozie, Nwosu; Aloh, Ngwuta; Ibiam, Okechukwu; Nwankwo, Felix; Ikpolo, Gabriel; Iwuala, Harrison (African Journal of Politics and Administrative Studies, 2024)
This work explored the dynamics of Nigeria-China relations from the political and economic points of view between 1999-2023. The primary concern of this paper is to discern the extent Nigeria-China relations is mutually beneficial and how Nigeria can stand to gain more if the relationship is properly aligned to Nigeria’s national interest. The central argument of this work is that Nigeria stands to gain more from China than from the West bearing in mind the fact that over one hundred years of Africa’s relationship with the West has been largely exploitative and disadvantageous. In this regard, the research employed both primary and secondary sources of data collection. The primary sources relied on first-hand information gathered from the Chinese Embassy as well as key actors within the Nigeria External Affairs Ministry and Key Informant Interviews on experts in Nigeria-China relations. The secondary sources relied on already existing information from libraries, text books, journals and the internet. The theoretical framework employed is the Complex Interdependence Theory. The conclusion drawn from this work is that Nigeria-China relations have not fully developed to the extent of being more beneficial to Nigeria economically and politically. What currently subsists is that China is gaining economically more in terms of trade to Nigeria’s disadvantage. However, politically and socio-culturally, the two countries are mutually benefiting due to various diplomatic protocols and cultural exchanges. The study recommended among others that Nigeria must strive to develop her techno-industrial export-oriented base to ensure more symmetric beneficial relationship with China.
Keywords: Bi-Lateral Relations; China; Development; Economic Development; Nigeria

The African Continental Free Trade Area (AfCFTA): Taking stock and looking ahead for international business research - Debrah, Yaw A.; Olabode, Oluwaseun E.; Olan, Femi; Nyuur, Richard B. (Journal of International Management, 2024)
The establishment of the African Continental Free Trade Area (AfCFTA) has opened new avenues of research interest in International Business and International Management. However, scholarly work in this fledgling area of research has been disparate and often lacking in the assessment of core international business implications of the emergence of the AfCFTA on member states as well as non-member states. This is because, as yet, no systematic attempt has been made to explore the AfCFTA in the context of IB research, or project future IB research directions. Hence, in this paper, using the PRISMA method we have systematically identified the current published research and scholarly work on the AfCFTA and provided a robust picture of the current state of knowledge and available literature on the AfCFTA while at the same time outlining potential areas for future international business research.
Keywords: AfCFTA; African Continental Free Trade Area; Informal cross-border trade; International business; Regional economic communities (RECs); Systematic literature review

How can the rule of law under the WTO framework ensure sustainable fishery governance through fishery subsidies? A study from the perspective of special and differential treatment - Bai, Jiayu; Wu, Yuting (Heliyon, 2024)
Background Considering the declining situation of sustainability in global marine fisheries, World Trade Organization (WTO) members successfully concluded the Agreement on Fisheries Subsidies(AFS) after 21 years of negotiations in 2022. As an the integral part of these negotiations, special and differential treatment (SDT) provisions provide developing countries with special rights and developed countries with the possibility to treat developing countries more favorably than other WTO members. Objective This study analyzed the role of SDT for fisheries subsidies in ensuring sustainable fishery governance by the rule of law, as well as the reflection of SDT under the AFS, to explore whether SDT can support sustainable fishery governance under the WTO framework. Methods This study is primarily based on official data and critical legal studies and used normative analysis and historical analysis to expose the essence of the SDT issue in the AFS as a political game in the legal form. Results The practical challenges in the implementation of SDT may affect the compliance willingness of member states. To overcome the obstacles, such as ambiguity and inefficiency, that impede the legalization process of sustainable global marine fishery governance, it is necessary to emphasize the value of SDT for the common interests of the WTO members in marine fisheries legislation. This will benefit the developing countries, especially the small island developing states, in the short term; and the common interests of developed and developing countries in the long term. Policy implications SDT facilitated the consensus between the developing and developed countries on issues such as illegal, unreported, and unregulated fishing subsidies and overfishing subsidies. However, current SDT practices have deviated from the original intention of the fairness and democratic approach of global marine fisheries governance, which should take into consideration the specific situation of developing countries.
Keywords: Agreement on fisheries subsidies; Overfishing; Rule of law; Special and differential treatment; Sustainable fishery governance; World Trade Organization

Property in goods and the CISG - Maier-Lohmann, Till (Fachmedien Recht und Wirtschaft, dfv Mediengruppe, 2024)
Keywords: CONTRACTS; INTERNATIONAL SALE OF GOODS; UN Convention on Contracts for the International Sale of Goods (1980)